Autoimmunity to βIV spectrin in paraneoplastic lower motor neuron syndrome - Berghs, Stanny (The National Academy of Sciences, 2001)
Paraneoplastic neurological disorders may result from autoimmunity directed against antigens shared by the affected neurons and the associated cancer cells. We have recently reported the case of a woman with breast cancer and paraneoplastic lower motor neuron syndrome whose serum contained autoantibodies directed against axon initial segments and nodes of Ranvier of myelinated axons, including the axons of motoneurons. Here, we show that major targets of the autoantibodies of this patient are βIVΣ1 spectrin and βIV spectrin 140, two isoforms of the novel βIV spectrin gene, as well as a neuronal surface epitope yet to be identified. Partial improvement of the neurological symptoms following cancer removal was associated with a drastic reduction in the titer of the autoantibodies against βIV spectrin and nodal antigens in general, consistent with the autoimmune pathogenesis of the paraneoplastic lower motor neuron syndrome. The identification of βIV spectrin isoforms and surface nodal antigens as novel autoimmune targets in lower motor neuron syndrome provide new insights into the pathogenesis of this severe neurological disease.